Educational and methodical function of the military physical fitness system and level of its scientific rationale - Nomerovskiy S.V (Kharkov National Pedagogical University, 2011)
The conceptual foundations of the methodical training in a system of the navy military physical training of Ukraine and well-developed countries are discussed. The comprehensive analysis of the literature in a field of methodical training of the military among 28 points, 12 of which are foreign is carried out. The modern conditions of the methodical training subsystem while the task of physical training solving is determined. The results of the analysis of system factors, which characterized the methodical training process towards management of special physical training amongst subordinates in a special conditions is shown. The experience of existing methodical training of the navy military of well-developed countries is summarized. The prospective issues of further scientific development are suggested.